2017
DOI: 10.1136/bmjopen-2016-014358
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on health-promoting lifestyle practices and information and communication technologies: scoping review protocol

Abstract: IntroductionInformation and communication technologies (ICTs) play a key role in improving health and maintaining health promoting behaviours. ICTs are therefore one potential solution for promoting healthy lifestyles. In addition, they can assist in the reduction and control of the menace of both communicable and non-communicable diseases. This study will map evidence of interventions that demonstrate the effect of ICTs on health-promoting lifestyle practices that can prevent and control diseases. It is antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Seventy per cent of global mortality has been attributed to NCDs 1 2. Eighty per cent of deaths associated with NCDs occur in low-income and middle-income countries (LMICs) in the 30–60 years age group 2–5. In 2013, a report showed that (Int$) 53.8 billion was spent on NCDs globally 6.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventy per cent of global mortality has been attributed to NCDs 1 2. Eighty per cent of deaths associated with NCDs occur in low-income and middle-income countries (LMICs) in the 30–60 years age group 2–5. In 2013, a report showed that (Int$) 53.8 billion was spent on NCDs globally 6.…”
Section: Introductionmentioning
confidence: 99%
“…Health-promoting lifestyle behaviour has been identified as having an essential role in prevention and control of NCDs 13–16. Health promotion is an umbrella term describing a composite of disease prevention and health promotion 3. Information and communication technology (ICT) has been shown to be beneficial as it has made it possible to access health-related information easily 17.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Management support for HPLB of staff is best shown by creating an enabling environment for health promotion activities as an integral part of organizational strategy (Milner et al, 2013). The concept of HPLB seems still to be new despite the role it plays in the prevention and control of NCDs (Tol et al, 2013;Joseph-Shehu & Ncama, 2017;WHO, 2017). Most of our participants regarded health facilities such as the NHIS as synonymous with 'sickness': resources to be used when you are ill or have a health complaint.…”
Section: Discussionmentioning
confidence: 99%